2009
DOI: 10.2134/agronj2008.0192x
|View full text |Cite
|
Sign up to set email alerts
|

Potato Response to a Polymer‐Coated Urea on an Irrigated, Coarse‐Textured Soil

Abstract: Controlled release fertilizers, especially polymer‐coated urea (PCU), have been shown to reduce nitrate (NO3) leaching while maintaining potato (Solanum tuberosum L.) yields, but cost has been prohibitive. A new type of PCU (Environmentally Smart Nitrogen, Agrium, Inc., Calgary, AB) is less costly than previous PCUs, but its effectiveness on potato production has not been extensively studied. A 2‐yr field study was conducted on loamy sand to evaluate the effect of this PCU on Russet Burbank tuber yield and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 35 publications
5
52
1
1
Order By: Relevance
“…Thus, the results obtained in this work with stabilized controlled release nitrogen fertilizer does not corroborate with what is indicated by Boman and Battikhi (2007), for whom the use of slow release nitrogen fertilizer reduces the need for parceling fertilizers.By parceling the application of the nitrogen sources in three times, independently of the management type adopted (surface and incorporated), the NH 3 volatilization decreases (C7 , Table 5). Wilson et al (2009) demonstrated a reduction in the need to split N application when using coated urea, which was not observed in our study.The cumulative NH 3 volatilization values as a function of collection time were adjusted to the logistic equation [Y = a/1+e…”
Section: Resultscontrasting
confidence: 80%
“…Thus, the results obtained in this work with stabilized controlled release nitrogen fertilizer does not corroborate with what is indicated by Boman and Battikhi (2007), for whom the use of slow release nitrogen fertilizer reduces the need for parceling fertilizers.By parceling the application of the nitrogen sources in three times, independently of the management type adopted (surface and incorporated), the NH 3 volatilization decreases (C7 , Table 5). Wilson et al (2009) demonstrated a reduction in the need to split N application when using coated urea, which was not observed in our study.The cumulative NH 3 volatilization values as a function of collection time were adjusted to the logistic equation [Y = a/1+e…”
Section: Resultscontrasting
confidence: 80%
“…Wen et al (2001) reported greater N recovery from coated than regular fertilizer, because N release better matched crop N demand and uptake. Controlled release fertilizers, especially polymercoated urea helped to reduce NO 3 -N leaching in potato (Solanum tuberosum L.) and may allow reduction of split N applications (Wilson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A two-year potato study on an irrigated loamy sand using Environmental Smart Nitrogen (ESN), polymer coated urea and a blend of urea and ammonium nitrate, found that optimum N rates were less for ESN than soluble N and potato yields under ESN were similar to those from split applied N (Wilson et al, 2009). In years with above average rainfall Wiedenfeld (1986) found that cabbage (Brassica oleracea L. Group capitata) and onion (Allium cepa L.) had increased yield, yield weight and leaf N content when grown with slow-release fertilizers, methylene urea and sulfur-coated urea, but there were no differences when rainfall was below average.…”
Section: Discussionmentioning
confidence: 99%